Les merveilles du scepticisme : René Descartes et les superhéros de comics - Chris Gavaler; Nathaniel Goldberg (ReS Futurae)
In his Meditations, Descartes introduces the idea of sceptical worries: I might be living in a dream or be the victim of an evil genius. These ideas are constantly emerging in science fiction, especially in superhero comics. Thus, through various comic books, such as Marvelman or Heroes Reborn, the authors illustrate that not only the Cartesian sceptical worries are displayed in the narratives, but they also expand them and dispelled the solution to scepticism provided by Descartes.